2001
DOI: 10.1093/carcin/22.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced S phase delay and inhibition of replication of an undamaged shuttle vector in UVC-irradiated xeroderma pigmentosum variant

Abstract: Xeroderma pigmentosum variant (XP-V) cells are defective in bypass replication of UVC-induced thymine dimers in DNA because they lack a novel DNA polymerase (polymerase eta). In this study the effects of UVC on S phase cells were compared in fibroblasts derived from normal donors (IDH4) and XP-V patients (CTag) and immortalized by expression of the SV40 large T antigen. These transformed fibroblasts did not activate the G(1) checkpoint or inhibit replicon initiation when damaged by UVC or gamma-rays. The trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…A previous report suggesting that ATM was involved in the S checkpoint response to low-dose UVC (52) was done with SV40-transformed fibroblasts. Human fibroblasts transformed with the SV40 large T antigen were recently reported to be defective in S checkpoint responses to both IR and UVC (8). SV40-transformed fibroblasts also display defective G 1 and G 2 checkpoint responses to IR (37).…”
Section: Discussionmentioning
confidence: 99%
“…A previous report suggesting that ATM was involved in the S checkpoint response to low-dose UVC (52) was done with SV40-transformed fibroblasts. Human fibroblasts transformed with the SV40 large T antigen were recently reported to be defective in S checkpoint responses to both IR and UVC (8). SV40-transformed fibroblasts also display defective G 1 and G 2 checkpoint responses to IR (37).…”
Section: Discussionmentioning
confidence: 99%
“…The C-Tag cells (POLH-deficient cells), which are SV40-immortalized cells derived from xeroderma pigmentosum-variant patients, were provided generously by Professor William K. Kaufmann (24).…”
Section: Methodsmentioning
confidence: 99%
“…We and other have previously shown that resumption of DNA synthesis after UVC irradiation is strongly impaired in the absence of polh [Bullock et al, 2001;Cordeiro-Stone et al, 2002;Despras et al, 2010]. In order to unravel the consequences of UBZ and PIP invalidation on S phase progression, cells were pulse-labeled with BrdU at various times after 7 J/m 2 and analyzed by flow cytometry (Supporting Information Fig.…”
Section: Resumption Of Dna Synthesis After Uvc Is Delayed In Single Mmentioning
confidence: 99%